Improved demethylation in ecological epigenetic experiments: Testing a simple and harmless foliar demethylation application. Issue 3 (16th October 2017) - Puy, Javier; Dvořáková, Hana; Carmona, Carlos P.; de Bello, Francesco; Hiiesalu, Inga; Latzel, Vít
Abstract: Experimental demethylation of plant DNA enables testing for epigenetic effects in a simple and straightforward way without the use of expensive and laborious DNA sequencing. Plants are commonly demethylated during their germination with the application of agents such as 5‐azacytidine (5‐azaC). However, this approach can cause unwanted effects such as underdeveloped root systems and high mortality of treated plants, hindering a full comparison with untreated plants, and can be applied only on plant reproducing by seeds. Here we test a simple alternative method of plant demethylation designed to overcome the shortcomings of the germinating method. We compared a novel method of demethylating plants, based on periodical spraying of 5‐azaC aqueous solution on established seedlings, with the previous method in which seeds were germinated directly in 5‐azaC solution. We quantified the amount of methylated DNA and measured various aspects of plant performance. Also, we demonstrated its applicability in ecological epigenetic experiments by testing transgenerational effects of plant–plant competition. We found that the spray application had similar DNA‐demethylating efficiency than the germination method, particularly in the earlier phases of plant development, but without unwanted effects. The spray application method did not reduce plant growth and performance compared to untreated plants, as opposed to the traditional method which showed reduced growth. Also, the spray application method equalized the epigenetically modified plant features of seedlings coming from plants grown under competition and plants growing without competition, demonstrating its application in ecological epigenetic experiments. We conclude that regular spraying of 5‐azaC solution onto established seedlings surpassed the germination‐in‐solution method in terms of vigour and fitness of treated plants. This novel method could thus be better suited for experimental studies seeking valuable insights into ecological epigenetics. Furthermore, the spray method can be suitable for clonal species reproducing asexually, and most importantly, it opens the possibility of community‐level experimental demethylation of plants.